The relationship between structure and in vitro antibacterial activity of selected isoflavones and their metabolites with special focus on antistaphylococcal effect of demethyltexasin - Hummelova, J; Rondevaldova, J; Balastikova, A; Lapcik, O; Kokoska, L (Letters in applied microbiology, 2015)
UNLABELLED: In this study, we tested 15 naturally occurring isoflavones and their metabolites for their possible antibacterial properties against nine Gram-positive and Gram-negative bacteria. The in vitro antibacterial activity was determined using the broth microdilution method, and the results were expressed as minimum inhibitory concentrations (MICs). 6,7,4'-trihydroxyisoflavone (demethyltexasin), 7,3',4'-trihydroxyisoflavone (hydroxydaidzein), 5,7-dihydroxy-4'-methoxyisoflavone (biochanin A), 7,8,4'-trihydroxyisoflavone (demethylretusin) and 5,7,4'-trihydroxyisoflavone (genistein) produced significant antibacterial activity (MICs ≥ 16 μg ml(-1)). The most effective compound, demethyltexasin, was subsequently tested for its growth-inhibitory effect against Staphylococcus aureus, and it exhibited significant antistaphylococcal effects against various standard strains and clinical isolates, including methicillin and tetracycline resistant ones with the MICs ranging from 16 to 128 μg ml(-1). SIGNIFICANCE AND IMPACT OF THE STUDY: The results of the structure-activity relationship (SAR) analysis identified ortho-dihydroxyisoflavones as a class of antibacterially effective compounds emphasizing the hydroxyl groups at C-5, 6 and 7 positions as crucial supposition for the antibacterial action of plant isoflavones and their metabolites. Demethyltexasin, an isoflavones' metabolite present in the human body through enterohepatic recycling of soya bean isoflavones (daidzein, genistein), showed the most potent antibacterial activity, especially against various strains of Staphylococcus aureus (including MDR and MRSA). The significance of this study is a deepening of the knowledge on isoflavones' SAR and identification of the antistaphylococcal activity of demethyltexasin, which suggest that metabolites of isoflavones can be even more potent antibacterial agents than their precursors.
Keywords: minimum inhibitory concentration; Methicillin; Anti-Bacterial Agents; Gram-Negative Bacteria; isoflavonoids; rostlinné extrakty; Microbial Sensitivity Tests; gramnegativní bakterie; Staphylococcus aureus; genistein; isoflavony; Isoflavones; vztahy mezi strukturou a aktivitou; Humans; demethyltexasin; antibakteriální látky; antimicrobial activity; methicillin-resistant Staphylococcus aureus; Plant Extracts; mikrobiální testy citlivosti; Genistein; Structure-Activity Relationship; lidé; methicilin